In Silico Study of Entry Inhibitor from Moringa oleifera Bioactive Compounds against SARS-CoV-2 Infection - Mawaddani, Nala (Springer, 2022)
The aim of this study is to screen the content of bioactive compounds of Moringa oleifera and to identify its potential as an antiviral against COVID 19 through an entry inhibitor mechanism using bioinformatics tools. The sample was obtained from PubChem database. Amino acis sequences were obtained from the NCBI. Protein modeling is made through the SWISSMODEL site. The target proteins for this study were SARS-CoV-2 M pro and RdRp. The protein-inhibitory interaction of the drug from M. oleifera bioactive compounds to SARS-CoV-2 was predicted by molecular docking with PyRx software. The result shows that M. oleifera was a potential antiviral candidate for SARS-CoV-2 with an entry inhibitor mechanism through a compound, especially quercetin. The RFMS value of both interactions between Mpro and quercetion and RdRp with quercetin were not higher than 1.05. This result still needed further research to prove this prediction.